A construção de um sistema de propriedade intelectual com características chinesas: uma análise do campo de propriedade intelectual no plano Made in China 2025 - Soares, Manuela Müller (Universidade do Vale do Rio dos Sinos, 2025)
The present research aims to analyze how Intellectual Property (IP) was incorporated as a strategic component of China's industrial policy within the framework of the Made in China 2025 plan, guided by the research question: "How did China incorporate Intellectual Property into its industrial development strategy within the scope of the Made in China 2025 plan?" Adopting Qin Yaqing's Relational Theory of International Relations, which interprets politics as a process of historical and relational co-constitution. The methodology relies on the analysis of official documents, such as the Made in China 2025 plan and reports from the China National Intellectual Property Administration (CNIPA) and the World Intellectual Property Organization (WIPO), in addition to reference texts on relational theory. The results demonstrate that the incorporation of IP was proactive and strategic, elevating the protection of intangible assets to a resource of national power essential for technological self-sufficiency. In this conjuncture, the Made in China 2025 plan utilized national legislative reforms, adherence to WIPO-administered treaties, and multilateral projection through WIPO, the Belt and Road Initiative (BRI), and the BRICS as tools for relational management, integrating IP into a long-term vision for China's transformation into a global technological power within an intellectual property system "with Chinese Characteristics."
Keywords: Propriedade intelectual; China; Política internacional; Política externa chinesa; Intellectual property; International politics; Chinese foreign policy